Chemical Composition and Antimicrobial Activities of Three Satureja Species Against Food-borne Pathogens. Issue 8 (16th November 2016) - Saharkhiz, Mohammad Jamal; Zomorodian, Kamiar; Taban, Azin; Pakshir, Keyvan; Heshmati, Keyvan; Rahimi, Mohammad Javad
Abstract: Foods provide a natural and perfect medium for bacteria and fungi to multiply and growth. Awareness of people of synthetic additives and preservatives in food processing has led food industries to search for natural additives with a broad spectrum of antimicrobial activities. The chemical compositions of the essential oils (EOs) distilled from three Satureja spp. have been analyzed by gas chromatography-mass spectrometry (GC-MS). The antimicrobial activities of the EOs against microorganisms causing food-borne infections were determined by the broth micro-dilution method as recommended by the Clinical and Laboratory Standards Institute (CLSI). Analysis of the EOs showed that phenolic compound including thymol and carvacrol are the main components of the EOs. Inhibition studies indicated that the tested EOs entirely inhibited the growth of tested fungi at concentrations of less than 0.062 μl/mL. Moreover, the oils exhibited significant bacteriostatic and bactericidal activities against Gram-positive and Gram-negative bacteria at concentrations ranging from 0.031–1 μL/mL. Considering the wide range of antimicrobial activities of the examined EOs, they might have potential to be used in food industry as a natural preservative agent and to extend the shelf life of products.